Membangun Semangat Kerja Dengan Loyalitas Dan Kepercayaan Diri Pada Pegawai - Yakup yakup; Anggita Permata Yakup (Center for Economic Studies Universitas Katolik Parahyangan, 2019)
This study aims to analyze work morale by increasing the loyalty and self-confidence of the employees of Jalaludin Airport, Gorontalo. The research data was obtained through distributing questionnaires that originated from questionnaires filled out by respondents. The population and research sample are employees with a total sample of 87 people. Method used for research analysis was multiple linear regression. The data was processed using Statistical Product and Service Solutions (SPSS) applications. The data analysis begins with testing the quality of the data through the validity and reliability of the research data. Hypothesis testing is done partially and simultaneously. The results of the research analysis found that employees’ morale can be built or improved by strengthening work loyalty and self-confidence in employees. If employees have high work loyalty and are supported by high self-confidence, then employees’ morale will increase. Keywords: Spirit at work; Job Loyalty; Confidence